FEATURES OF COMPASSION IN THE FAMILY UPBRINGING OF CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article explains how ancient customs and traditions acted on raising and upbringing children. And also to create a family today, parents should not be limited only by the requirements of modern life, but also meet the requirements of Sharia in due time. Since spiritual understanding in the family of children increases their moral qualities and worldview, which is one of the main directions in state policy.